DAKWAH RELASI AGAMA (STUDI PRELIMINARI BERBASIS Al-QUR’AN) - Iftitah Jafar; Mudzhira Nur Amrullah (Fakultas Dakwah dan Komunikasi, 2019)
This paper reveals da‘wa of interfaith relation based on the Qur’an. It is a qualitative preliminary research. The study analyzes Qur’anic verses on da‘wa through the implementation of thematic approach. The results showed that: 1. This form of da‘wa is designed based on six considerations: 1. Islam is a universal religion (Q.21:107), 2. Islam promotes international communication (Q.49:13), 3. Islam acknowledges religious disparities (Q.5:48) and (Q.11:118), 4. Islam strongly emphasizes in respecting religious differences (Q.17:70). 5. Islam encourages people to live competitively (Q.5:48). 6. Qur’an encourages Muslims to be fair towards other religious followers (Q.5:8). The aim of da‘wa as follows: 1. Communities understand the Qur’anic concept of interfaith relation, 2. Communities acknowledge the existence of other religions, 3. Communities may live peacefully and harmoniously. In addition, the methods of da‘wa of interfaith relation, namely: 1. Religious counseling, 2. Religious dialogue, 3. Da‘wa of action, and 4. Da‘wa of assistance.